El embargo en el derecho registral ecuatoriano: implicaciones y seguridad jurídica - Gonzaga Sierra, Javier Fernando (2025)
The embargo in Ecuadorian registration law is a fundamental legal institution to guarantee legal security in real estate transactions. This study analysed how this procedure affects the rights of creditors, debtors and third parties involved in these transactions. The Ecuadorian regulations related to the seizure were reviewed, including the Civil Code, the Registration Law, and the General Organic Code of Procedures, as well as the relevant jurisprudence. The main challenges in the uniform application of these regulations were identified, such as the lack of consistency in the registration of embargoes and the need to modernize the registration system. The investigation also included a comparative analysis with the registration systems of Spain and Argentina, highlighting the best practices that could be implemented in Ecuador. The results suggest that, although the Ecuadorian regulatory framework provides a solid basis for the protection of rights, it is necessary to improve the efficiency and consistency in the application of these regulations to ensure the legal certainty of all parties involved.